Stored platelets alter glycerophospholipid and sphingolipid species, which are differentially transferred to newly released extracellular vesicles. Issue 3 (15th July 2012) - Pienimaeki‐Roemer, Annika; Ruebsaamen, Katharina; Boettcher, Alfred; Orsó, Evelyn; Scherer, Max; Liebisch, Gerhard; Kilalic, Dzenan; Ahrens, Norbert; Schmitz, Gerd
<x xml:space="preserve">Abstract</x> BACKGROUND: Stored platelet concentrates (PLCs) for transfusion develop a platelet storage lesion (PSL), resulting in decreased platelet (PLT) viability and function. The processes leading to PSL have not been described in detail and no data describe molecular changes occurring in all three components of stored PLCs: PLTs, PLC extracellular vesicles (PLC‐EVs), and plasma. STUDY DESIGN AND METHODS: Fifty PLCs from healthy individuals were stored under standard blood banking conditions for 5 days. Changes in cholesterol, glycerophospholipid, and sphingolipid species were analyzed in PLTs, PLC‐EVs, and plasma by mass spectrometry and metabolic labeling. Immunoblots were performed to compare PLT and PLC‐EV protein expression. RESULTS: During 5 days, PLTs transferred glycerophospholipids, cholesterol, and sphingolipids to newly formed PLC‐EVs, which increased corresponding lipids by 30%. Stored PLTs significantly increased ceramide (Cer; +53%) and decreased sphingosine‐1‐phosphate (−53%), shifting sphingolipid metabolism toward Cer. In contrast, plasma accumulated minor sphingolipids. Compared to PLTs, fresh PLC‐EVs were enriched in lysophosphatidic acid (60‐fold) and during storage showed significant increases in cholesterol, sphingomyelin, dihydrosphingomyelin, plasmalogen, and lysophosphatidylcholine species, as well as accumulation of apolipoproteins A‐I, E, and J/clusterin. CONCLUSION: This is the first detailed analysis of lipid species in all PLC components during PLC storage, which might reflect mechanisms active during in vivo PLT senescence. Stored PLTs reduce minor sphingolipids and shift sphingolipid metabolism toward Cer, whereas in the plasma fraction minor sphingolipids increase. The composition of PLC‐EVs resembles that of lipid rafts and confirms their role as carriers of bioactive molecules and master regulators in vascular disease.